Functional domain studies uncover novel roles for the ZTL Kelch repeat domain in clock function. - Ann Feke; Morgan Vanderwall; Wei Liu; Joshua M Gendron (PLoS ONE)
The small LOV/F-box/Kelch family of E3 ubiquitin ligases plays an essential role in the regulation of plant circadian clocks and flowering time by sensing dusk. The family consists of three members, ZEITLUPE (ZTL), LOV KELCH PROTEIN 2 (LKP2), and FLAVIN-BINDING KELCH REPEAT F-BOX PROTEIN 1 (FKF1), which share a unique protein domain architecture allowing them to act as photoreceptors that transduce light signals via altering stability of target proteins. Despite intensive study of this protein family we still lack important knowledge about the biochemical and functional roles of the protein domains that comprise these unique photoreceptors. Here, we perform comparative analyses of transgenic lines constitutively expressing the photoreceptor LOV domain or the Kelch repeat protein-protein interaction domains of ZTL, FKF1, and LKP2. Expression of each domain alone is sufficient to disrupt circadian rhythms and flowering time, but each domain differs in the magnitude of effect. Immunoprecipitation followed by mass spectrometry with the ZTL Kelch repeat domain identified a suite of potential interacting partners. Furthermore, the ZTL Kelch repeat domain can interact with the ZTL homologs, LKP2 and FKF1, and the LOV domain of ZTL itself. This suggests a hypothesis that the Kelch repeat domain of ZTL may mediate inter- and intra-molecular interactions of the three LOV/F-box/Kelch proteins and provides added insight into the composition of the protein complexes and an additional role for the Kelch repeat domain.